Biodegradation of plastics in soil and effects on nitrification activity. A laboratory approach - Bettas Ardisson, Giulia; Tosin, Maurizio; Barbale, Marco; Degli-Innocenti, Francesco (Frontiers in Microbiology, 2014)
The progressive application of new biodegradable plastics in agriculture calls for improved testing approaches to assure their environmental safety. Full biodegradation (≥ 90%) prevents accumulation in soil, which is the first tier of testing. The application of specific ecotoxicity tests is the second tier of testing needed to show safety for the soil ecosystem. Soil microbial nitrification is widely used as a bioindicator for evaluating the impact of chemicals on soil but it is not applied for evaluating the impact of biodegradable plastics. In this work the International Standard test for biodegradation of plastics in soil (ISO 17556, 2012) was applied both to measure biodegradation and to prepare soil samples needed for a subsequent nitrification test based on another International Standard (ISO 14238, 2012). The plastic mulch film tested in this work showed full biodegradability and no inhibition of the nitrification potential of the soil in comparison with the controls. The laboratory approach suggested in this Technology Report enables (i) to follow the course of biodegradation, (ii) a strict control of variables and environmental conditions, (iii) the application of very high concentrations of test material (to maximize the possible effects). This testing approach could be taken into consideration in improved testing schemes aimed at defining the biodegradability of plastics in soil.